Seismic behavior of high-rise modular steel constructions with various module layouts. (September 2020) - Shi, Fengwei; Wang, Haipeng; Zong, Liang; Ding, Yang; Su, Junsheng
Abstract: Owing to their superiority in construction speed and quality, modular steel constructions (MSCs) are extensively used in low-rise buildings in non-seismic regions. Even in areas where the lateral load resistance is not demanding, fully modular steel constructions are not applicable unless additional lateral resistant members are introduced, such as cast-in-situ concrete cores or prefabricated steel frames. The primary focus of this research is to study the seismic behavior of high-rise MSCs with various module layouts, thereby enhancing the flexibility and feasibility of high-rise MSCs in regions of high seismicity. Five three-dimensional (3D) high-rise MSCs with various module layouts, i.e., parallel stacked (Configuration 1), one end staggered (Configuration 2), both ends staggered (Configuration 3), intermediately staggered (Configuration 4), and vertically staggered (Configuration 5), were designed. Seismic analyses were carried out in terms of these five models through response spectrum and elastic-plastic time-history analyses. The natural vibration characteristics of various module layouts show that vibration periods of the first three vibration modes are essentially the same (except Configuration 3), which meets the limit requirement. The first two vibration modes are translational deformation along the X and Z directions, and the third mode is torsional, indicating that MSCs can present excellent integrity with Configurations 1, 2, 4, and 5. Structural deformations show that staggered layouts (Configurations 2–5) can solve the problem of inconsistent bidirectional stiffness in Configuration 1. Through discussing the advantages and disadvantages of different module layouts, this paper provides a preliminary knowledge basis for applications of fully high-rise MSCs in seismic regions. Highlights: Five 3D high-rise MSCs with various module layouts were introduced. 3D response spectrum and elastic-plastic time history analyses were performed. The seismic behavior of 20-story modular steel constructions (MSCs) was evaluated. Structural optimization suggestions of high-rise MSCs with various module layouts were provided.